Green alignment, green vocational education and training, green skills and related subjects : a literature review on actors, contents and regional contexts - Pilz, Matthias [Verfasser] (My University, 2025)
“This study conducts an exploratory and integrative literature review to investigate the discourse on various concepts and terms related to the green alignment of vocational education and training (VET). The study focuses on the key actors setting the discourse, the content within it and the regional contexts in which the discourse occurs. A review of 85 international publications reveals that the discourse is predominantly shaped by the perspectives of policy and research, with international organisations playing a prominent role in the policy strand. While green skills are primarily associated with green jobs in the labour market, green VET encompasses the process of greening VET providers. This discourse appears to be especially prevalent in the Asia-Pacific region and in Africa. The results of the study provide policy and research actors with a nuanced understanding of the discourse, enabling policy actors to integrate scientific insights more effectively into their decision-making processes and foster a more constructive dialogue between policy and research.“ (authors’ abstract; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; 370; Berufsbildung; Berufsausbildung; Green skills / Grüne Kompetenzen; Begriff; Internationaler Vergleich; Literaturanalyse